Matrilin‐2 prevents the TNFα‐induced apoptosis of WB‐F344 cells via suppressing JNK pathway. (29th January 2019) - Luo, Junming; Peng, Shaohua; Bai, Wenbin; Wu, Zhaoyu; Shan, Zhongshu; Wu, Zetao; Yuan, Xin; Che, Xiaoming; Duan, Zhili; Peng, Jinwu; Wang, Yichun; Zhang, Shukun
Abstract: Oval cells, a kind of hepatic progenitor cell quiescent at normal condition, activates to proliferate and differentiate into hepatocytes under severe and long‐term liver injury, which usually raises severe inflammation. However, how oval cell survives in the inflammatory milieu interne is still unclear. Tumor necrosis factor α (TNFα), mimicking inflammatory hepatic milieu interne, was used to treat oval cell line, WB‐F344, to test the protective function of matrilin‐2. In this study, our data suggested that matrilin‐2 prevented TNFα‐induced apoptosis in WB‐F344 cells via inhibiting ASK1/MKK7/JNK pathway. In conclusion, we determined that matrilin‐2 plays the key role in maintaining the survival of oval cell and guarantees its proliferation under various injury factors.